Molluscum Contagiosum of Cervix – A Case Report - Bagel, Ankita (J Clin Diagn Res, 2017)
Molluscum Contagiosum (MC) is a common viral infection of skin caused by a double stranded DNA Pox virus affecting both adults and children. MC is primarily an infection of school-going children (one to five years), occasionally it affects adults and immunocompromised individuals. Transmission of virus occurs by direct contact with infected persons or contaminated objects. Most common sites are skin of face, trunk and extremities in children, genitals in adults and rarely palms, soles and mucous membranes. The occurrence of MC in genitals is lowest (3%). We present a case report of Molluscum Contagiosum of cervix which is a rare site; only one case has been reported in medical literature till date.